Hostility to hospitality: spirituality and professional socialization within medicine - Balboni, Michael J. (Oxford University Press, 2019)
A rising hostility in American medicine -- The spiritual event of serious illness -- Spirituality and end-of-life outcomes -- The frequency of spiritual care at the end of life -- What hinders spiritual care? empirical explanations -- Social structures separating medicine and religion -- The secular-sacred divide in medicine -- Defining religion and spirituality -- Toward a theology of medicine -- Theology within the patient-clinician relationship -- The sacramental nature of medicine -- A spirituality of immanence -- Why medicine should resist immanence -- Problematic rapprochement strategies -- Structural pluralism for medicine and religion -- From hostility to hospitality